An Experiment Study of Head-to-Media Spacing Sensitivity in Ultra-high Density Magnetic Recording Systems - Pichet Nhunork; Chanon Warisarn; Damrongsak Tongsomporn (My University, 2016)
The decrease in flying height due to the higher recording areal density of hard disk drives (HDDs) has had a huge impact on data storage technology. The head protrusion that induced by ambient temperature can further reduce flying clearance by a few nanometers. However, the head-disk interface reliability should be also emphasized; since when the head flies too close to the media, the recording head may be burnished. To investigate the head-to-media spacing sensitivity, we use the spin stand tester and analyze the sensitivity through the measurement of overwrite (OVW), micro-track profile (MTP), and signal-to-noise ratio (SNR). The experiment results imply the significant relationship between the OVW and the heater-induced writer protrusion (H-IWP). Furthermore, we verify that the properly reduction of head-to-media spacing can also enhance the both of writability and readability.
Keywords: Flying height; Patterned media; Area density; Optical disc; Recording media; SIGNAL (programming language); Recording head; Magnetic properties of thin films